Clinical phenotypes, endotypes, and biomarker profiles of immediate rituximab hypersensitivity reactions: a prospective pharmacovigilance study - Narapong Yotinnoratham; Wannada Laisuan; Kumutnart Chanprapaph; Silada Kanokrungsee; Chavachol Setthaudom; Supornchai Onpun; Pungjai Mongkolpathumrat; Supranee Buranapraditkun; Apinya Chungcharoenpanich; Nichapha Dechapaphapitak; Supa Oncham; Nattakirana Tongdee; et al. (Frontiers in Allergy, 2026)
Background Rituximab (RTX) has been associated with immediate hypersensitivity reactions (HSRs) involving multiple phenotypes and endotypes. Objective To characterize the clinical phenotypes and endotypes of immediate RTX HSRs. Methods A prospective study was conducted as part of a pharmacovigilance program from July 2020 to December 2021. Participants who experienced immediate RTX HSRs were enrolled. Skin testing, basophil activation testing (BAT), IFN- γ ELISpot assays, and IgG anti-drug antibody (ADA) ELISA assays were performed. Results Seventeen patients with immediate RTX reaction were enrolled, including 9 with infusion-related reactions (IRRs) and 8 with immediate RTX HSRs. Among 13 patients who underwent biomarkers testing, all 5 patients with IRRs showed negative result for all biomarkers. Among the eight patients with immediate RTX HSRs, elevated serum tryptase levels during acute reaction onset were observed in four patients, suggesting possible type I reaction, although definite classification was limited by the reaction. Two of the 8 patients demonstrated elevated IL-6 levels together with increased serum tryptase levels, suggesting mixed reactions (type I/CRS). The remaining 4 patients could not be assigned to a specific endotype and were therefore categorized as unclassified. BAT results were negative in all cases. Conclusion Immediate RTX HSRs demonstrated heterogeneous phenotypes and endotypes. IRRs were the most common phenotype and occurred exclusively during the first RTX cycle. Skin testing, ADA detection, and serum IL-6 measurement may contribute to endotype characterization, although larger prospective studies are needed to establish their diagnostic utility.